2016
DOI: 10.1371/journal.pone.0155535
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors of European Syndromic Surveillance Systems: A Worked Example of Applying Qualitative Comparative Analysis

Abstract: IntroductionSyndromic surveillance aims at augmenting traditional public health surveillance with timely information. To gain a head start, it mainly analyses existing data such as from web searches or patient records. Despite the setup of many syndromic surveillance systems, there is still much doubt about the benefit of the approach. There are diverse interactions between performance indicators such as timeliness and various system characteristics. This makes the performance assessment of syndromic surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Hospitalbased surveillance of respiratory viral infections is of great value to understand the full disease spectrum, from mild symptoms to serious presentations. Children are the most avid transmitters of respiratory viral infections, and the information gained from syndromic surveillance in children's hospitals can complement decentralized sentinel surveillance systems in a meaningful way [133]. With the advent of rapid diagnostics and mobile health applications, it has now become possible to monitor virological and clinical end points in real time [134][135][136][137][138][139][140].…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalbased surveillance of respiratory viral infections is of great value to understand the full disease spectrum, from mild symptoms to serious presentations. Children are the most avid transmitters of respiratory viral infections, and the information gained from syndromic surveillance in children's hospitals can complement decentralized sentinel surveillance systems in a meaningful way [133]. With the advent of rapid diagnostics and mobile health applications, it has now become possible to monitor virological and clinical end points in real time [134][135][136][137][138][139][140].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has examined the potential for syndromic surveillance to detect disease outbreaks earlier than other forms of public health surveillance [7,38]. In the present review, the evidence to support these claims is limited with regard to a mass gathering scenario.…”
Section: Discussionmentioning
confidence: 94%
“…A provisional diagnosis, or "syndrome," can be established via the synthesis of clinical features, disease trends, and surrogate measures (e.g., derived from pharmaceutical sales and doctor visits, among others) [6]. Syndromic surveillance has been shown to be a potentially effective method for the early detection of seasonal outbreaks of influenza as well as other pathogens, and previous research has shown the viability of this surveillance strategy for detecting larger outbreaks (>1000 symptomatic cases) [7,8]. Additionally, syndromic surveillance is potentially useful in occupational scenarios, where emerging threats such as COVID-19 or influenza pose a risk to workplace staff [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The successful PEDSIDEA pilot programme demonstrates that surveillance systems for influenza can be set‐up quickly enabling individualized patient data analysis in epi/pandemics . Stakeholders will receive real‐time information on influenza incidence and severity, allowing the allocation of resources where they are most in need.…”
Section: Discussionmentioning
confidence: 99%
“…This paper aims to present a simple, standardized way of measuring clinical outcomes in children at the time of initial presentation to allow for meaningful comparisons across clinical settings. It invites other clinicians to use these standardized measures as well, to improve the monitoring of quality of care, to understand overall disease burden and the prevalence of risk factors, and finally, to explore the relationship between severity and prescribing practices, cost, and other outcome measures of interest.The successful PEDSIDEA pilot programme demonstrates that surveillance systems for influenza can be set-up quickly enabling individualized patient data analysis in epi/pandemics 3,22. Stakeholders will receive real-time information on influenza incidence and severity, allowing the allocation of resources where they are most in need.…”
mentioning
confidence: 99%